Multiculturalism Humans Rights and Public Policies (Docentes 2.0 Journal, 2023)
The universal postulates of peace, human rights, and governability in the Rule of Law with peaceful societies facilitate justice for its inhabitants. The present work focused on accrediting the design of protection and management systems to guarantee the fundamental rights of individuals. The interpretative processes were supported by an action-research method, socio-critical paradigm, hybrid approach, collaborative design, practical and cross-sectional. The State of Mexico was the setting for its cultural diversity; the sample was 20 projects of the human rights plan for 2021; The findings were triangulated to verify their scope, which made it possible to assess the attributes in terms of management and results in direct interviews. Regarding the results, the collaborative actions with a civil society made it possible to promote legal advice to attend to victims in situations of vulnerability and sensitizing groups susceptible to discrimination; in total, there were 35,627 individuals in the implementation of the plan. On the other hand, the complaints for transgression were for acting authorities by preventing the relief of administrative processes. The instances of arbitrariness were those persecuted by trade 74% and local governments 15%. At the country level, the National Human Rights Commission reported that 3,483 authorities from various fields acted arbitrarily. The multicultural dynamic entails the deformation of public policies to implement new management archetypes in understanding.
Keywords: Humans rights; evaluation; management; multiculturalism; public policies